(3QSGFd CNhGf GdUaGs ((3CUdGf Hf GSeGYjd RZHi s)
(3ChdgG (B:s
(3agQSJ jJVef eG JMhi gPg GdChQGb ef QSGFd ENhGf GdUaG hNdGf GdhaG hCgd GdJhMjO hgj CQHYI CbSGe aefgG QjGVjI JYdjejI hefgG LSeGfjI WHjYjI hefgG faSGfjI YbdjI hefgG cdjI GdCdgjI s
(3BNQgG (B:s
(3hGYde jG CNj HCfc bGUO QHc ef jhe NdbJ fWaI ai GdQMef hQHWJ HgG faSc fLRJ GdQSGdI GdYGTQI ef GdbSe GdKGdK s
(3HgG fXGe GdJYbjHIs
(3GdeNWhW YHGQI Yf YTQI QSGFd ef GdbSe GdKGdKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B902s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs